Freio eletromagnético para ensaios de motores elétricos de indução - Pereira, Adriano Holanda (2006)
In this work, through the use of a variable mechanical load, tests are realized in two squirrel cage asynchronous motors. For that, it is presented the desigh and the implementation of a electromagnetic brake by the eddy currents action, according to analytic proposals for the calculation of the braking torque. Measurements of the real power, power factor, current and speed for all nominal operation range of the two 10 hp motors are realized. From the experimental comparative and of two different mathematical models, ABC model and single- phase equivalent circuit, the best performance of the high efficiency induction motor is evidenced.